2013
DOI: 10.1074/jbc.m113.492520
|View full text |Cite
|
Sign up to set email alerts
|

A Brain-specific Grb2-associated Regulator of Extracellular Signal-regulated Kinase (Erk)/Mitogen-activated Protein Kinase (MAPK) (GAREM) Subtype, GAREM2, Contributes to Neurite Outgrowth of Neuroblastoma Cells by Regulating Erk Signaling

Abstract: Background:We previously identified GAREM1 as a downstream adaptor of the EGF receptor. Results: GAREM2 is a brain-specific GAREM subtype that is also tyrosine-phosphorylated and binds Grb2. Conclusion: GAREM2 is a regulator of neurite outgrowth of neuroblastoma cells in the presence of IGF-1. Significance: This study demonstrates the biological function of the GAREM family proteins, including their expression and subcellular localization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 40 publications
(48 reference statements)
0
30
0
Order By: Relevance
“…anguillicaudatus . The garem and emp2 , which positively regulate and promote cell proliferation and division 27 , 28 , were positively selected in the M . anguillicaudatus clade, and the similar results were also observed in the previous study 12 , suggesting cell proliferation also act as a critical factor in the environmental adaptation in M .…”
Section: Discussionmentioning
confidence: 99%
“…anguillicaudatus . The garem and emp2 , which positively regulate and promote cell proliferation and division 27 , 28 , were positively selected in the M . anguillicaudatus clade, and the similar results were also observed in the previous study 12 , suggesting cell proliferation also act as a critical factor in the environmental adaptation in M .…”
Section: Discussionmentioning
confidence: 99%
“…THEMIS and THEMIS2 are present in all mammals, whereas THEMIS3 is absent in primates. Two single CABIT module proteins are also expressed in mammals; GAREM1 which is broadly expressed [31] and GAREM2 which is expressed in neuronal cells [32]. GAREM1, GAREM2 and most other single CABIT module proteins also contain a Sterile alpha motif (SAM) putative protein interaction domain (Fig.…”
Section: The Themis Enigmamentioning
confidence: 99%
“…THEMIS and THEMIS2 are functionally interchangeable since transgenic expression of THEMIS2 rescued the developmental defect in Themis −/− mice [8]. The single CABIT module mammalian proteins GAREM1 (GRB2-associated and regulator of MAPK1, subtype 1) and GAREM2, are positive regulators of ERK signaling in response to epidermal growth factor (EGF) receptor engagement [31, 32]. Nevertheless, it was reported that ERK activation, calcium flux, NFATC2 nuclear translocation and other effector responses [15] are enhanced in Themis −/− thymocytes under sub-maximal TCR/co-receptor stimulation conditions [14, 15].…”
Section: Reconciling the Models: The Tcr Signaling Conundrummentioning
confidence: 99%
“…SORBS2 is involved in several biological pathways (Table 2). Sorbin, the product of SORBS2, is an ArgBP2 protein and SH3 domain-containing protein 2 and might be involved in insulin-mediated translocation of GLUT4 and thereby might affect energy storage [47]. Previous research has highlighted the role of this functional protein in disease states [48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%